EXAMINING CONVENIENCE, WEBSITE DESIGN & SOCIAL INFLUENCE AS DETERMINANTS OF USERS’ INTENTION TO USE FINTECH SERVICES - Shunmugasundaram, V; Srivastava, Shanu (Indian Journal of Finance and Banking, 2023)
An amalgamation of the financial sector with information technology has brought a tremendous transformation in the financial services sector that resulted in FinTech, which is an invention that makes it easier and more convenient for users to conduct financial transactions digitally. So, the present study aims to examine Convenience (C), Website Design (WB) & Social Influence (SI) as the determinants of users’ Intention to Use (ITU) FinTech Services. For the study, we collected data through a survey instrument using the hybrid mode of data collection from 257 FinTech users. Data analysis and hypotheses testing was done by using SmartPLS 4 software. The findings of the study concluded that determinants namely, Convenience (C), Website Design (WB) & Social Influence (SI) have a significant positive influence on users’ Intention to Use (ITU) FinTech Services. Hence, all hypotheses framed in the study were accepted. The outcome of this study will facilitate FinTech service providers to design more specialized services for their consumers. Further, it contributes to the literature concerned with the FinTech service sector and antecedents of ITU FinTech services. JEL Classification Codes: G41, O30, O31, 033.